2018
DOI: 10.1080/09537104.2018.1430358
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and interpreting platelet-leukocyte aggregates

Abstract: Platelets, besides their specialised role in haemostasis and atherothrombosis, actively modulate innate and adaptive immune responses with crucial roles in immune surveillance, inflammation and host defence during infection. An important prerequisite for platelet-mediated changes of immune functions involves direct engagement with different types of leukocytes. Indeed, increased platelet-leukocyte aggregates (PLAs) within the circulation and/or locally at the site of inflammation represent markers of many thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 129 publications
2
105
0
1
Order By: Relevance
“…The formation of platelet-leukocyte aggregates is now recognized as a sensitive marker of in vivo platelet activation and is a feature of inflammatory conditions 30 , 44 , 45 . These aggregates are mediated via multiple ligands and receptors including P-selectin which is translocated to the surface of activated platelets 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of platelet-leukocyte aggregates is now recognized as a sensitive marker of in vivo platelet activation and is a feature of inflammatory conditions 30 , 44 , 45 . These aggregates are mediated via multiple ligands and receptors including P-selectin which is translocated to the surface of activated platelets 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the interaction between leukocytes and platelets was facilitated by the use of flow cytometric analysis and advanced microscopy techniques [30]. However, characteristics of PLAs in terms of size and number of platelets bound per leukocytes are not well defined.…”
Section: Inflammation and Platelet-leukocyte Interactionsmentioning
confidence: 99%
“…Images showing PLAs as investigated by flow cytometry, tissue section or live cell imaging were presented by Finsterbush et al in their review on platelet-leukocyte interactions in acute ischemic stroke, renal diseases, and hepatic as well as lung inflammation and infection. They suggested that PLAs within the circulation or locally at the sites of inflammation might represent markers of many thrombo-inflammatory diseases and could be used for the assessment of both thrombotic risk and disease progression [30]. Moreover, PLAs could be of great interest as markers of the modulation of thrombo-inflammation in patients receiving antithrombotic drugs in the setting of acute inflammation.…”
Section: Inflammation and Platelet-leukocyte Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis has long been viewed as an immunologically-driven disease, in which different leukocytes and T cells play important roles. Although platelet interactions with leukocytes have been reported for psoriasis mouse models and are typically found in many other inflammatory diseases (Ludwig et al, 2004;Tamagawa-Mineoka, 2015;Finsterbusch et al, 2018), a specific role for platelets in the skin lesions of psoriasis patients has not been noted. In agreement with the systemic inflammatory nature of psoriasis, we found platelet-PMN and –monocyte aggregates in the circulation to correlate with the disease in the skin.…”
Section: Discussionmentioning
confidence: 99%